Lessons to Learn From Low-Dose Cyclosporin-A: A New Approach for Unexpected Clinical Applications - Flores, Camila; Fouquet, Guillemette; Moura, Ivan Cruz; Maciel, Thiago Trovati; Hermine, Olivier (Frontiers in Immunology, 2019)
Cyclosporin-A has been known and used for a long time, since its “fast track” approval in the early 80’s. This molecule has rapidly demonstrated unexpected immunosuppressive properties, transforming the history of organ transplantation. Cyclosporin’s key effect relies on modulation on T-lymphocyte activity, which explains its role in the prevention of graft rejection. However, whether cyclosporin-A exerts other effects on immune system remains to be determined. Until recently, cyclosporin-A was mainly used at a high-dose, but given the drug toxicity and despite the fear of losing its immunosuppressive effects, there is nowadays a tendency to decrease its dose. The literature has been reporting data revealing a paradoxical effect of low dosage of cyclosporin-A. These low-doses appear to have immunomodulatory properties, with different effects from high-doses on CD8+ T lymphocyte activation, auto-immune diseases, graft-versus-host disease and cancer. The aim of this review is to discuss the role of cyclosporin-A, not only as a consecrated immunosuppressive agent, but also as an immunomodulatory drug when administrated at low-dose. The use of low-dose cyclosporin-A may become a new therapeutic strategy, particularly to treat cancer.